Fountains of wisdom in conversation with James H. Charlesworth - Charlesworth, James H. 1940- (T&T Clark, 2022)
"Leading international contributors on biblical texts, including the New Testament and the Dead Sea Scrolls, intersect with the work of James H. Charlesworth and examine Charlesworth’s vast contribution to the field of biblical studies, honoring the work of one of the most significant biblical scholars of his generation. Divided into five sections, this volume begins with a section on the Hebrew Bible and the New Testament texts, with particular focus on the Gospel of John and Jesus studies. The contexts of these texts are considered, with a focus on the Greco-Roman and Jewish worlds, and the varying intersections between texts and the worlds that created them. The contributors then focus on the most significant body of Charlesworth’s work, the apocrypha/pseudepigrapha and the Dead Sea Scrolls, and the journey concludes with an assessment of the history of scholarship on the core areas addressed across the book."
Includes bibliographical references and index
Keywords: Bible / Criticism, interpretation, etc; Bible / Apocrypha / Criticism, interpretation, etc; Dead Sea scrolls / Criticism, interpretation, etc; Apocryphal books / Criticism, interpretation, etc